Principles of transaction processing - Bernstein, Philip A. (Morgan Kaufmann series in data management systems., 2009)
"Principles of Transaction Processing, Second Edition offers a clear, concise guide for anyone involved in developing applications, evaluating products, designing systems, managing databases, or engineering products. It provides an understanding of the internals of transaction processing systems, describing how they work and how best to use them. It includes the architecture of application servers, transactional communications paradigms, and mechanisms for recovering from transaction and system failures."--Jacket.